More Than Expected From Old Sponge Samples: A Natural Sampler DNA Metabarcoding Assessment of Marine Fish Diversity in Nha Trang Bay (Vietnam) - Turon, Marta; Angulo-Preckler, Carlos; Antich, Adrià; Præbel, Kim; Wangensteen, Owen S. (Frontiers in Marine Science, 2020)
Sponges have recently been proposed as ideal candidates to act as natural samplers for environmental DNA due to their efficiency in filtering water. However, validation of the usefulness of DNA recovered from sponges to reveal vertebrate biodiversity patterns in Marine Protected Areas is still needed. Additionally, nothing is known about how different sponge species and morphologies influence the capture of environmental DNA and whether biodiversity patterns obtained from sponges are best described by quantitative or qualitative measures. In this study, we amplified and sequenced a vertebrate specific 12S barcode with a set of universal PCR primers (MiFish) for metabarcoding environmental DNA from fishes, to unveil fine-scale patterns of fish communities from natural-sampler DNA retrieved from 64 sponges (16 species) located in eutrophic and well-preserved coral reefs in Nha Trang Bay (central Vietnam). 90 tropical fish species were identified from the sponges, corresponding to one third of the total local ichthyofauna reported from previous extensive conventional surveys. Significant differentiation in fish communities between eutrophic and well-preserved environments was observed, albeit eutrophication only explained a modest proportion of the variation between fish communities. Differences in efficiency of capturing fish environmental DNA among sponge species or morphologies were not observed. Overall, the majority of detected fish species corresponded to reef-associated small-sized species, as expected in coral reefs environments. Remarkably, pelagic, migratory, and deep-sea fish species were also recovered from sponge tissues, pointing out the ability of sponge natural sampled DNA to detect fishes that were not permanently associated to the biomes where the sponges were sampled. These results highlight the suitability of natural samplers as a cost-effective way to assess vertebrate diversity in hyper-diverse environments.